The effects of organizational quality management initiatives and mediating factor on the sustainability of Malaysian higher education institutions - Ayodele, Lasisi Abass (Kulliyyah of Education, International Islamic University Malaysia, 2016)
The purpose of this study is to examine the relationship between the organizational quality management initiatives and mediating factor on the Sustainability of Malaysian Higher Education Institutions (SMHEI). The quality assurance initiative (QAI), long term strategic planning initiatives (LSPI) and balanced scorecard initiatives (BSCI) theory were measured and assessed through the organizational climate (OC) on the SMHEI. The study utilized 272 top administrators' completed questionnaire survey out of 600 targeted distributions to 20-year old universities in Malaysian Peninsula. The statistical techniques employed in this study were involved Descriptive statistics using SPSS version 20.0, Confirmatory Factor Analysis (CFA) and a full-fledged Structural Equation Modeling (SEM) with software Analysis of Moment Structures (AMOS) version 20.0 to addresses the research questions and as to test the research hypotheses. As organizational quality management initiative is one of the government's priorities, a policy in Malaysian Higher Education Institutions (MHEI), the findings reveal that Long term Strategic Planning Initiatives (LSPI) need to be revisited. Similarly, communication and decision-making in organizational climate of MHEI remain challenging towards the improvement of SMHEI. Consistently, implementing of BSCI could enhance the achievement of effectiveness and efficiency on the SMHEI. Theoretically, the study found that not only campus or leadership perspectives are requiring investigation and it also needs to be extended to financial, customer, internal process, and learning and growth perspectives in the administration for SMHEI. There are some implications from study which need the top management embraced as adjustment. As this is first research of its kind in Malaysia, the value for sustainability of MHEI will be of important for national growth agenda. In conclusion, this study has contributed to knowledge in this field, closed the gap in the literature on Sustainability of Higher Education Institutions (SHEI) and it served as improvement and awareness for Ministry of Higher Education, Malaysia. Additionally, adjustment on quality service for both private and public universities in Malaysia is needed. This study recommends more studies on additional underlying constructs and authenticates the developed model on SMHEI.